Fifteen years of ChEMBL and its role in cheminformatics and drug discovery - Barbara Zdrazil (Journal of Cheminformatics)
Abstract In October 2024 we celebrated the 15th anniversary of the first launch of ChEMBL, Europe’s most impactful, open-access drug discovery database, hosted by EMBL’s European Bioinformatics Institute (EMBL-EBI). This is a good moment to reflect on ChEMBL’s history, the role that ChEMBL plays in Cheminformatics and Drug Discovery as well as innovations accelerated using data extracted from it. The review closes by discussing current challenges and possible directions that need to be taken to guarantee that ChEMBL continues to be the pioneering resource for highly curated, open bioactivity data on the European continent and beyond.